No association between dopamine D3 receptor gene Ser9Gly polymorphism (rs6280) and risk of schizophrenia: an updated meta-analysis - Qi XL (Dove Medical Press, 2017)
Xing-ling Qi, Jin-feng Xuan, Jia-xin Xing, Bao-jie Wang, Jun Yao School of Forensic Medicine, China Medical University, Shenyang, People’s Republic of China Objective: Ser9Gly (rs6280) is a functional single-nucleotide polymorphism (SNP) in the dopamine receptor D3 (DRD3) gene that may be associated with schizophrenia. We performed a meta-analysis to determine whether Ser9Gly influences the risk of schizophrenia and examined the relationship between the Ser9Gly SNP and the etiology of schizophrenia.Methods: Case–control studies were retrieved from literature databases in accordance with established inclusion criteria. Odds ratios (ORs) and 95% confidence intervals (CIs) were calculated to evaluate the strength of the association between Ser9Gly and schizophrenia. Subgroup analysis and sensitivity analysis were also performed.Results: Seventy-three studies comprising 10,634 patients with schizophrenia (cases) and 11,258 controls were included in this meta-analysis. Summary results indicated no association between Ser9Gly and risk of schizophrenia. In the dominant genetic model, the pooled OR using a random effects model was 0.950 (95% CI, 0.847–1.064; P=0.374).Conclusion: Results of this meta-analysis suggest that the Ser9Gly SNP is not associated with schizophrenia. These data provide possible avenues for future case–control studies related to schizophrenia. Keywords: dopamine receptor D3, schizophrenia, meta-analysis, gene polymorphism